Analisis Manajemen Risiko Bagian Hubungan Masyarakat pada Instansi Pemerintah - Bella Febiola; Wisnu Yuwono (Jurnal Bangkit Indonesia, 2023)
This research was conducted to determine risk management planning in government agencies that may occur in an organization's activities is an important aspect, where accuracy is required in uncovering the problems and underlying causes, as well as the various risks that will be faced. This study uses a literature study research method with a qualitative approach. The type of approach in this research is descriptive. The analysis technique used by the author here is to analyze risk management planning in the Public Relations section of Government Agencies which includes risk registers, risk events and triggers, Risk Breakdown Structure (RBS), risk response, and risk analysis. The results of this study indicate that there are four risks in the Public Relations Section of government agencies which include two low risks, one medium risk, and one high risk. Most risks are caused by a lack of planning and control. Therefore, the Public Relations Department needs to implement more effective and efficient planning and supervision to maintain the reputation of government agencies, increase public trust, and improve effectiveness and efficiency in conveying public information.